Responsabilidade social empresarial: o caso de uma indústria alimentícia no estado do Pará - Coelho, Izabel Cristina Martins (2010)
The theme of corporate social responsibility (CSR) provides discussion and analysis and relatively recent, particularly in the last twenty years, has grown into the world as well as in Brazil, the interest on the involvement of the business sector in social activities or projects facing combating poverty. However, a lack of socialization of successful experiences in the practice of CSR and clarity and consensus concepts generate deviations of understanding on the subject and the structuring of interventions. This research aimed to reveal how corporate social responsibility of the IMA Food was developed from Project Nursery Saci. The research took place under a qualitative approach of descriptive-explanatory, conducted through semi-structured interviews and non-participatory observation and interviewed 35 people in total. The interpretation and analysis of data occurred through a categorical content analysis, having as theoretical approach to socioeconomic CSR. The results showed that the major form of social responsibility of the Food IMA is based on a classical approach of CSR, focusing on philanthropy. The absence of a more systematic management of the project and reflect the fragility, instability and lack of commitment towards the community. The contributions generated by the project are substantial and important, but do not reach the development occasioned by the company. However, none of this invalidates the initiative of the organization's commitment to the community, however, requires a reassessment and restructuring of the proposal in a way that leverages the performance of the project and the company itself and it can more effectively contribute to society